Tests and Measurements of Hand Ball Attletsin Trenggalek Regency In Preparation for East Java PORPROV 2022 - Muhammad Soleh Fudin; Khamin Hariyadi (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
The purpose of developing sports science and technology is to improve the quality and quantity of knowledge and technology by utilizing proven scientific methods and theories. In the development of sports coaching to improve performance, there are many factors that must be carried out by sports as sports development coaching. One of the factors in the development of sports coaching is science in the field of sports which is commonly called sport science. Based on our observations and analysis, the training process in the Handball Puslatcab has not been optimal. The training delivered by the trainer does not yet have valid data on the physical condition of the handball athletes in Trenggalek Regency. In addition, the trainer's lack of understanding about measurement tests as material for evaluating athlete development. This condition has become the focus of the service team, namely assistance in the field of sport science, especially on the type of physical condition measurement test in handball training in Trenggalek Regency with athletes and coaches as targets for training evaluation. The form of service carried out is community assistance. While the approach to the implementation of service uses a participatory approach. The method of implementing the service that will be carried out with the partners of the ABTI Pengcab in Trenggalek Regency is a test of measuring the physical condition of athletes in the sport of handball. The results of the training assistance for handball athletes in Trenggalek Regency are the results of measurement tests in the form of athlete data along with a description of the recommendations related to the results of the data.